Challenges in radar sea clutter modelling. Issue 9 (7th May 2022) - Watts, Simon; Rosenberg, Luke
Abstract: The ability to detect small targets in sea clutter is still an ongoing challenge, even for modern radar systems. Over the past decade, the development of new radar waveforms and signal processing algorithms has been assisted by an increasingly good understanding of the characteristics of sea clutter. Nevertheless, many challenges remain in the development of robust sea clutter models that span the wide range of sea conditions and viewing geometries encountered in practice. This paper describes the current challenges with some suggestions on how they can be overcome.